THE ISSUE OF ENDING THE ILLITERACY OF WOMEN AND GIRLS IN TURKESTAN IS IN THE VIEWS OF THE JADIDS - Muhayyo Ganijonovna Ergasheva (Galaxy International Interdisciplinary Research Journal, 2022)
One of the biggest events in the historical processes of our country is the question of bringing women from the legal unconscious form of the national mentality to the level of literacy, which has existed for centuries. This article presents a reasonable study of the positive assessment of the issue of female illiteracy in Turkestan by the intellectuals of the same nation and the fact that this attitude is faced with different opinions.